Rituximab resistant evans syndrome and autoimmunity in Schimke immuno-osseous dysplasia - Rosik Tomas; Simankova Nadezda; Dusek Jiri; Seeman Tomas; Sukova Martina; Balascakova Miroslava; Guillén-Navarro Encarna; Levtchenko Elena; Baradaran-Heravi Alireza; Krepelova Anna; Zieg Jakub; Skalova Sylva; et al. (BMC, 2011)
Abstract Autoimmunity is often observed among individuals with primary immune deficiencies; however, the frequency and role of autoimmunity in Schimke immuno-osseous dysplasia (SIOD) has not been fully assessed. SIOD, which is caused by mutations of SMARCAL1, is a rare autosomal recessive disease with its prominent features being skeletal dysplasia, T cell deficiency, and renal failure. We present a child with severe SIOD who developed rituximab resistant Evans syndrome (ES). Consistent with observations in several other immunodeficiency disorders, a review of SIOD patients showed that approximately a fifth of SIOD patients have some features of autoimmune disease. To our best knowledge this case represents the first patient with SIOD and rituximab resistant ES and the first study of autoimmune disease in SIOD.